The Effect of Linker Group on Thermoelectric Properties of Dimer Zinc Porphyrin-Based Molecular Junctions - Preesam, Dhia; Noori, Mohammed; Moghaddam, Hossain (University of Thi-Qar Journal of Science, 2023)
The discovery of high-efficiency organic thermoelectric materials has the potential to pave the path for various energy-harvesting technologies and the development of flexible, transparent thin-film materials for Peltier coolers. Our study involves a comparison of the electrical and thermoelectric characteristics of four zinc porphyrin configurations. The results show that changing the linker between zinc diner units has an essential effect on the electrical conductance and thermopower values of these structures. Consequently, the thermoelectric figure of merit ZT will change which means the thermoelectric efficiency change.